NF-kappaB Activation in Esophageal Adenocarcinoma: Relationship to Barrett's Metaplasia, Survival, and Response to Neoadjuvant Chemoradiotherapy - KELLEHER, DERMOT P; WINDLE, HENRY (Lippincott Williams & Wilkins, 2004)
OBJECTIVE: To examine the expression of the transcription factor nuclear factor kappa B (NF-kappaB) in Barrett's epithelium and adenocarcinoma and the impact of NF-kappaB expression on tumor stage and response to neoadjuvant chemotherapy and radiation therapy. SUMMARY BACKGROUND DATA: Progression of Barrett's esophagus to adenocarcinoma is associated with a wide range of cellular and molecular abnormalities. Nuclear factor-kappa B (NF-kappaB) regulates several genes involved in inflammatory, immune and apoptotic responses, but its role in esophageal inflammation and tumorigenesis has not been reported. METHODS: Mobility shift assay was used to measure NF-kappaB activity in nuclear extracts of fresh-frozen biopsies from tumor and uninvolved tissues (n = 30) and esophageal cell lines OE33, SKGT-4, and OE21. RelA expression was assessed by immunohistochemical staining (n = 97). The NF-kappaB/RelA and IkappaB protein expressions were also examined by Western blotting. RESULTS: NF-kappaB was not expressed in normal esophageal squamous epithelium, in contrast to increased expression in 40% of patients with Barrett's epithelium. Sixty-one percent of resected tumors (n = 97) displayed NF-kappaB immunoreactivity, and 87.5% of the NF-kappaB-positive tumors were Stage IIb and III compared with only 12.5% of patients with Stage I and IIa disease (P < 0.05). The expression of NF-kappaB inversely correlated with major or complete pathologic responses to neoadjuvant chemotherapy and radiation therapy, with 15/20 (75%) responders in the NF-kappaB-negative group compared with 7/38 (18%) in the NF-kappaB-positive group (P < 0.00001). Moreover, incubation of esophageal cell lines OE33, SKGT-4, and OE21 with deoxycholic acid or low pH induced NF-kappaB expression. CONCLUSIONS: Bile acids and low pH induce NF-kappaB expression in esophageal cell lines. NF-kappaB activation is common in esophageal adenocarcinoma. In patients with Barrett's epithelium and an associated esophageal adenocarcinoma, there is a progressive expression of NF-kappaB through Barrett's tumorigenesis. The absence of NF-kappaB expression in esophageal adenocarcinoma correlates with response to neoadjuvant chemoradiotherapy and may be of value in predicting response to neoadjuvant therapy.
PUBLISHED
Keywords: Clinical Medicine